Antioxidants Special Issue: Peroxiredoxin 6 as a Unique Member of the Peroxiredoxin Family - Aron B. Fisher (MDPI AG, 2019)
The peroxiredoxins, first discovered about 30 years ago, are the most recently described family of ubiquitously expressed antioxidant enzymes [...]